Mechanomyography in assessing muscle spasticity: A systematic literature review - Muhamad Aliff Imran, Daud; Asmarani Ahmad Puzi, asmarani@iium.edu.my; Shahrul Na’im, Sidek; Salmah Anim, Abu Hassan; Ahmad Anwar, Zainuddin; Ismail, Mohd Khairuddin; Mohd Azri, Abdul Mutalib (Penerbit UMP, 2024)
Mechanomyography (MMG) has gained significant prominence in the domain of scientific inquiry, exhibiting widespread applications in diverse areas including sensor advancement, signal processing methodologies, characterization of muscle spasticity, diagnosis of neurological disorders, and as a valuable tool in medical rehabilitation. However, despite the considerable body of existing MMG research, there remains a paucity of comprehensive investigations in these domains in the past. The primary objective of this systematic review is to conduct a comprehensive analysis of the available literature pertaining to the evaluation of muscle spasticity assessment using mechanomyography (MMG) in a systematic and categorical manner. By applying the pre-established search criteria to five prominent databases, a total of 63 pertinent studies that met the inclusion criteria for our review. Through a thorough scrutiny of the 10 meticulously selected records, we unveiled the extensive diversity in protocols and parameters employed in the assessment of muscle spasticity using mechanomyography (MMG). Accelerometers and piezoelectric sensor used for mechanomyography (MMG) are currently in the nascent phase of their development, as evidenced by the findings of this systematic review. Notably, this review also highlights the influence of sensor placement on muscles as a potential factor affecting the acquired signal. In consideration of these findings, it can be concluded that further research is warranted to advance MMG, particularly in the domains of sensor refinement, with specific attention to accelerometers, and the refinement of signal processing techniques. Additionally, future investigations should aim to expand the scope of MMG applications in clinical settings and rehabilitation practices.